2021
DOI: 10.3390/app112311278
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Physicochemical Properties of Chitin Extracted from Cicada orni Sloughs Harvested in Three Different Years and Characterization of the Resulting Chitosan

Abstract: Chitin and its derivative chitosan are among the most used polysaccharides for biomedical and pharmaceutical applications. Most of the commercially available chitin is obtained from seafood wastes. However, the interest in alternative renewable sources of chitin and chitosan, such as insects, is growing. When new sources are identified, their stability over time has to be evaluated to allow for their commercialization. The aim of this study is to compare the physicochemical properties of chitin extracted from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
3
1
Order By: Relevance
“…The Ic of these samples was due to the salt crystallinity, as explained above. The Ic of the freeze-dried Ch solution prepared with water was quite lower than that determined by Poerio et al [ 37 ], which analyzed Ch samples produced in laboratory scale and calculated Ic = 53.7%. Indeed, the XRD spectrum determined by Poerio et al [ 37 ] showed a very broad and tall first peak, different from that observed in the present work, thus explaining this high crystallinity.…”
Section: Resultscontrasting
confidence: 63%
See 1 more Smart Citation
“…The Ic of these samples was due to the salt crystallinity, as explained above. The Ic of the freeze-dried Ch solution prepared with water was quite lower than that determined by Poerio et al [ 37 ], which analyzed Ch samples produced in laboratory scale and calculated Ic = 53.7%. Indeed, the XRD spectrum determined by Poerio et al [ 37 ] showed a very broad and tall first peak, different from that observed in the present work, thus explaining this high crystallinity.…”
Section: Resultscontrasting
confidence: 63%
“…The X-ray diffraction (XRD) spectrum of the freeze-dried Ch solution prepared with water ( Figure 3 ) presented peaks at approximately 2θ= 11.2° and 20.2°, referring to 020 (crystal 1) and 110 (crystal 2) planes, respectively, typical of Ch [ 4 , 37 ]. The XRD spectrum of samples prepared with 0.2% of Ac ( Figure 3 b) presented these same peaks, confirming that not all amounts of Ch were solubilized.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, amide II and amide III bands are characteristic of fungal material [ 27 , 38 ]. Here, the crust spectrum differs from the other spectra indicating a higher degree of deacetlyation of chitin [ 39 41 ]. The bands at lower wavenumbers (1200 cm -1 –800 cm -1 , green frame) can be attributed to polysaccharides, such as glucans, with a maximum at ~1023 cm -1 for the crust indicating α-glucan, and a maximum at ~1038 cm -1 for the hymenium, trama, and mycelial core indicating the presence of β-glucan [ 27 , 40 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…The chitin characteristic peak is indicated by a shoulder near 3100 cm −1 , which is attributed to N-H stretching [ 36 ] and shoulder at 1025 cm −1 , which correspond to β-1,4-glycosidic linkage [ 35 , 48 ]. Other chitin characteristic bands are located and are hidden by protein bands at 1538 cm −1 (NH), 1375 cm −1 (CH 3 ) and 1312 cm −1 (CN) [ 40 , 51 ]. The shoulder near 3100 cm −1 is slightly more strongly pronounced in C. guilliermondii , C. lusitaniae and S. pastorianus after treatment with organic solvents.…”
Section: Resultsmentioning
confidence: 99%